2021
DOI: 10.33774/chemrxiv-2021-sp3fs
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Understanding the Crucial Significance of the Temperature and Potential Window on the Stability of Carbon Supported Pt-alloy Nanoparticles as Oxygen Reduction Reaction Electrocatalysts

Abstract: The present research provides a comprehensive study of carbon-supported intermetallic Pt-alloy electrocatalysts and assesses their stability against metal dissolution in relation to the operating temperature and the potential window using two advanced electrochemical methodologies: (i) the in-house designed high-temperature disk electrode (HT-DE) methodology as well as (ii) a modification of the electrochemical flow cell coupled to an inductively coupled plasma mass spectrometer (EFC-ICP-MS), allowing for high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 64 publications
2
10
0
Order By: Relevance
“…Plus, higher temperature might positively impact the exophilic nature of the electrocatalysts used. [50,51] However, a thorough study to explain this significant influence is needed, since Faraday's first law of electrolysis has theoretically neglected the dependent towards electrolysis temperature.…”
Section: Current Work On Glycerol Ecrmentioning
confidence: 99%
See 1 more Smart Citation
“…Plus, higher temperature might positively impact the exophilic nature of the electrocatalysts used. [50,51] However, a thorough study to explain this significant influence is needed, since Faraday's first law of electrolysis has theoretically neglected the dependent towards electrolysis temperature.…”
Section: Current Work On Glycerol Ecrmentioning
confidence: 99%
“…This equation shows that as T increases or E a decreases (as electrocatalysts are equipped), the rate constant (K) will be increased which is directly proportional to the rate of the chemical reaction and hence, making it useful for calculating the rate law parameters. Yet, from authors' knowledge, there is still wide knowledge gap that exist related to the synergistic effect between the operating temperature with the nature of electrocatalysts (its E a and structural changes), [50,51] within glycerol ECR.…”
Section: Effect Of Reaction Temperaturementioning
confidence: 99%
“…Namely, it has been clear for some time that an increase in UPL strongly affects the stability of carbon-supported Pt-nanoalloys, both in terms of carbon support corrosion 47 and metal dissolution. 23,39,[57][58][59][60] Moreover, in terms of metal dissolution, in our recent work 42 it has been shown that at a constant high temperature (75 o C),…”
Section: Introductionmentioning
confidence: 96%
“…Specifically, the fuel cell electrocatalysts are exposed to very aggressive conditions, including a corrosive environment, high temperatures, humidity, frequent stops and starts, fluctuations in the operational voltage, and so forth. 9 These non-intrinsic operational conditions, together with the intrinsic properties of the electrocatalyst (choice of M, 23 order/disorder, 22 de-alloying/activation, 36 type of carbon/degree of graphitization 37 ), lead to a spectrum of very complex and interconnected degradation mechanisms: (i) electrochemically induced (transient) dissolution of Pt, which is defined by thermodynamic tendency of Pt to the formation/reduction of the Pt-oxide, [38][39][40][41] resulting in Ostwald ripening 42,43 and/or formation of metallic Pt-bands in the membrane, [44][45][46] (ii) dissolution of M 23,42 and (iii) electrochemical and chemical carbon support corrosion, [47][48][49] leading to the agglomeration and/or detachment of whole Pt NPs. These complex instability phenomena are of crucial importance for the longevity of the PEMFCs in the case of their application in both light-duty vehicles (LDVs) beside heavyduty vehicles (HDVs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation